Music technology with Swing : 13th International Symposium, CMMR 2017, Matosinhos, Portugal, September 25-28, 2017, Revised selected papers /: 13th International Symposium, CMMR 2017, Matosinhos, Portugal, September 25-28, 2017, Revised selected papers. (2018) - Unknown
No abstract available